Iggrot Ha’Ari Volume 1 - Berman, Shmuel; Barth, Daniel; Vorchheimer, Hannah; Dayanim, Ezra; Bane, Serena; Kanefsky, Alison; Tokayer, Jackie; Brunnlerhman, Joshua (Iggrot Ha’Ari, 2021)
Iggrot Ha’Ari is an open-access, undergraduate research-based journal that publishes multidisciplinary articles related to Jewish scholarship and religious thought. Iggrot Ha’Ari translates to “The Lion’s Letters.” The word “lion” reflects Columbia University’s mascot, Roar-ree, while the language of “letters” is a reference to the rabbinic tradition of respona. Together under advisory from the Institute for Israel and Jewish Studies, Iggrot Ha’Ari aims to promote Jewish knowledge and to provide students with the ability to academically master topics relevant to their own religious identity. Iggrot Ha’Ari hopes to provide readers with opportunities to create networks of scholars among authors and editors and foster relationships founded on Jewish scholarship.